HUBUNGAN PRESTASI BELAJAR AL-QUR’AN HADITS DENGAN PRESTASI BELAJAR AKIDAH AKHLAK SISWA KELAS IV MADRASAH IBTIDAIYAH AL-ZAYTUN - Hairun M. Rois; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
Akidah akhlak and Al-Quran Hacdist are important subjects in Madrasah. Professional teachers are required to be able to lead student to achieve maximum outcomes in their teaching and learning class activities. This study aims to examines the relationship between learning achievement of Al- Qur'an Hadith and akidah akhlak fourth graders of Madrasah Ibtidaiyah Al-Zaytun. The research employes method of quantitative research using a correlation approach. The object of this research is the fourth graders. Rresearch procedures or data collection techniques used are interviews and documentation. The results of the study found that students learning achievement Al- Qur'an hadith has a positive and significant learning achievement.